Effects of vineyard management and landscape context on taxonomic diversity and interaction networks of flower-visiting insects in the Cape Floristic Region biodiversity hotspot - Kehinde, Temitope Olatayo (Stellenbosch : Stellenbosch University, 2011)
Thesis (PhD)--Stellenbosch University, 2011.